GJB2 mutations causing autosomal recessive non-syndromic hearing loss (ARNSHL) in two Iranian populations: Report of two novel variants. (April 2018) - Koohiyan, Mahbobeh; Hashemzadeh-Chaleshtori, Morteza; Salehi, Mansoor; Abtahi, Hamidreza; Reiisi, Somayeh; Pourreza, Mohammad Reza; Noori-Daloii, Mohammad Reza; Tabatabaiefar, Mohammad Amin
Abstract: Objective: Hereditary hearing loss (HL) is a noticeable concern in medicine all over the world. On average, 1 in 166 babies born are diagnosed with HL in Iran, which makes it a major public health issue. Autosomal recessive non-syndromic HL (ARNSHL) is the most prevalent form of HL. Although over 60 genes have been identified for ARNSHL, GJB2 mutations are the most prevalent causes of ARNSHL in many populations. Previous studies have estimated the average frequency of GJB2 mutations to be between 16 and 18% in Iran, but would vary among different ethnic groups. In the present study, we aimed to determine the frequency and mutation profile of 70 deaf patients from two different provinces (center and west) of Iran. Methods: We enrolled 70 Iranian deaf patients with ARNSHL from Isfahan (40 family) and Hamedan (30 family) provinces. After extraction of genomic DNA, the entire coding region of GJB2 was directly sequenced in all patients. Multiplex PCR was used for detection of del( GJB6 -D13S1830) and del( GJB6 -D13S1854) in the GJB6 gene. In silico analyses were also performed by available software tools. Results: A total of eleven different mutations were detected, nine of which were previously reported and the other two (c.130T > G and c.178T > G) were novel. Homozygous GJB2 mutations were observed in 22.5% and 20% of all the subjects from Isfahan and Hamedan provinces, respectively. c.35delG was the most frequent mutation. One compound heterozygous genotype (c.358_360delGAG/c.35delG) was observed for c.35delG. Screening for the two GJB6 deletions did not reveal any positive sample among heterozygous or GJB2 negative samples. Conclusions: The present study suggests that mutations in the GJB2 gene specially c.35delG are important causes of ARNSHL in the center and west of Iran. Totally, 15% of the patients were heterozygous carriers. Further investigation is needed to detect the genetic cause of HL in the patients with monoallelic GJB2 mutations.